THE PROBLEMATIC OF PUBLIC DISCOURSE AND COMMUNICATIVE ETHICS WITHIN SOCIETY - Noureddine Anani (International Journal of Innovative Technologies in Social Science, 2025)
Interest in language continues to grow daily, as its users increasingly recognise its importance in communication on the one hand and its ability to dissolve ideological distances and bridge geographical separations on the other hand. This attention stems from a desire to transform language from mere words, signals, and gestures into a vital medium for exchange, deliberation, and coexistence. The concept of the public sphere is no less significant than language; it constitutes the centre of communicative action where mechanisms of dialogue and discussion are formed around the goal of common interest. This shared objective, in turn, weaves a fabric of civic values such as tolerance, social cohesion, and respect for diversity and difference. Communicative reasons were established politically, socially, and ethically in response to the qualitative crisis experienced by Western countries due to modernity. The centrality of the individual in Western thought gave rise to a self-referential crisis that acknowledged only itself and entirely negated the notion of the other. This individualism and class division ultimately stripped humans of their freedom. Amid this turmoil, pragmatics emerged as a linguistic revolution that overturned contemporary concepts, shifting language from its formal role to the core of the communicative process. A consensus emerged that language and understanding are interconnected concepts clarified through mutual exchange. Accordingly, a set of questions arises: Is communicative ethics truly capable of breaking away from instrumental rationality, or is it merely another form of instrumentalism and ideology, albeit in a new guise? If not, can communicative ethics and dialogue resolve the crisis of coexistence within the public sphere?